2008
DOI: 10.1177/0741932507311634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prerecorded Sight Words on the Accuracy of Tutor Feedback

Abstract: Six kindergarten students at risk for reading difficulties were taught to tutor each other and provide accurate feedback with the use of a prerecorded sight word model. Students were taught the components of reciprocal peer tutoring and were asked to tutor each other on unknown, phonetically irregular sight words. An A-B-A-B reversal design embedded within a multiple baseline design showed that prerecorded sight words increased students' accurate feedback during peer tutoring and testing. In addition, most stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…In addition, research has demonstrated the effectiveness of peer or parent tutoring with low-tech audio prompting to support a naïve tutor and improve limited-English-proficient preschoolers' English vocabulary (Cooke, Mackiewicz, Wood, & Helf, 2009) and kindergartners' acquisition of sight words (Van Norman & Wood, 2008). The present study extended the use of technology support in tutoring to another device, the VoicePod.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In addition, research has demonstrated the effectiveness of peer or parent tutoring with low-tech audio prompting to support a naïve tutor and improve limited-English-proficient preschoolers' English vocabulary (Cooke, Mackiewicz, Wood, & Helf, 2009) and kindergartners' acquisition of sight words (Van Norman & Wood, 2008). The present study extended the use of technology support in tutoring to another device, the VoicePod.…”
Section: Discussionmentioning
confidence: 77%
“…By using a peer tutoring procedure, teachers are able to extend targeted instruction to more students. In addition, academic gains were realized for both partners, adding to literature on reciprocal peer tutoring (e.g., Hughes & Fredrick, 2006;Mastropieri et al, 2001;Van Norman & Wood, 2008).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Children generalized from pictures to real objects. AP with reciprocal tutor feedback has also been used to increase the accuracy of sight words in kindergarteners (Van Norman & Wood, 2008) and to improve vocabulary with peer tutoring for 9- to 11-year-old students (Mackiewicz et al, 2011). AP can be used with a computer or tablet, making it readily available, inexpensive, practical, and easy to use.…”
Section: Apmentioning
confidence: 99%